Literackie narracje o kolekcjach - Skorupa, Ewa (Tematy i Konteksty, 2017)
The article concerns collections and collecting as a literary theme. Research on this issue should be undertaken by literary scholars, as collections support the characteristics of literary characters and give heroes their identity. The work analyzed from this angle is Money by Andrzej Strug from the year 1914. It interprets and describes three different collections and three different collectors: the eccentric Lyttons and their museum of stones, Lucy Slazenger’s precious jewelry collection and the art collection of Osias Murwaya, an enthusiast of antiquity.